Learning in the Digital Age During the COVID-19 Pandemic for School Improvement - Bih Ni Lee (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: Digital learning became increasingly popular when the COVID-19 disaster hit. Even though, its implementation is still less popular after no special indicators are used to create systematic learning. Comprehensive access to online education with fifth generation (5G) mobile technology coverage will enhance the quality of learning in the face of the digital age. Contribution: The contribution of this study is to increase the awareness of online learning during the COVID-19 pandemic. It recognizes the importance of strengthening online learning when schools close. It also highlights digital technologies and practices for school improvement and enters an endemic era. Method: Synthesis method. Researcher synthesized information naturally to help others see connections between things. Results: The presence of the COVID-19 threat has opened a new norm in pedagogical methods in Malaysia. The use of technology has long been championed since 2013. Its importance became apparent after the emergence of the pandemic in early 2020. Not because of pandemic had to give way to technology but the times need change according to the currents of modernity and high technology. Since then, we have faced the threat of a pandemic and through a life of new norms.  The convenience of computers and smartphones has changed the current learning process. Conclusion: The COVID-19 pandemic has affected the structure of Learning and Teaching in Malaysian educational institutions. Education institutions were also instructed to close and the live or face-to-face method of Learning and Teaching was changed to fully online Learning and Teaching. The education system will undergo changes of learning in the digital age. Digital learning also continues to be the new norm of pedagogy in the future.